Isolation And Identification Of Pathogen Mushroom Types On Umbi Talas (Colocasia Esculenta (L.) Schoot) Post Harvest - Fitria Dewi Sulistiyono; Tri Saptari Haryani (Universitas Pakuan, 2018)
The taro tuber (Colocasia esculenta) is an important source of carbohydrates for an important energy producer whose portion has a fairly bright and profitable development prospect. Taro is not only used as a food source, it can be used for industrial purposes, for example raw materials of cosmetics and plastic. Taro is very easy to recognize and varied with other preparations because it has a distinctive flavor. Increased production is the only major consideration in taro cultivation. Efforts to increase production are influenced by limiting factors that are often experienced in the community. Such barrier is a pathogen attack both on the ground and post harvest. The purpose of this study is to isolate and identify the types of pathogenic fungi found in taro tubers. The method used is microscopic and macroscopic identifications. The results of identification with the macroscopic and microscopic observations obtained by the genus Aspergillus, Candida, Sclerotium, Fusarium, Mucor, and Rhizopus. Keywords: Taro, Identification, Pathogenic Fungi